Prenatal Depression Severity and Postpartum Care Utilization in a Medicaid Population - Susan G. Kornstein; Anny-Claude Joseph; Whitney C. Graves; Jordyn T. Wallenborn (Mary Ann Liebert, 2020)
Background: Postpartum visits are a necessary continuum of medical care for women who are diagnosed with depression during pregnancy. However, postpartum care utilization is typically lower in populations who face adverse events and it is unclear to what extent having depression during pregnancy may compromise postpartum visit follow-up. Our study examined the association between severity of prenatal depression and postpartum care utilization among women on Medicaid. Materials and Methods: Data from a university-based, nonprofit managed care organization (2008?2012) were analyzed (N?=?846). Prenatal depression severity and postpartum care utilization were determined using the International Classification of Diseases, Ninth Revision (ICD-9) codes, from medical claims records. Bivariate and multivariable logistic regression was conducted. Odds ratios and 95% confidence intervals (CIs) were calculated. Results: The majority (64.2%) of women received a mild/moderate prenatal depression diagnosis and 52.5% of the total sample attended their postpartum care visit. After adjusting for confounders, we found decreased odds of postpartum care utilization among women with less severe diagnoses. Women with a mild/moderate prenatal depression diagnosis were 12% less likely to attend the postpartum care visit compared with women with a severe prenatal depression diagnosis (adjusted odds ratio?=?0.88, 95% CI?=?0.65?1.19). However, this finding was not statistically significant. Conclusions: Our study did not yield evidence of a statistically significant relationship between prenatal depression severity and postpartum visit attendance among a sample of Medicaid beneficiaries. Additional research is needed to assess the association between prenatal depression severity and postpartum care use to enhance continuity of services for Medicaid-insured women into the postpartum period.